Descartes on Natural Signs and the Case of Sensory Perception (Journal of Modern Philosophy)
Descartes used the notion of sign to describe three phenomena: language, the external movements of the passions, and sensory perception. For this, he appealed to conventional, external, and natural signs respectively. A systematic treatment of signs as proper components of Descartes’ considered views is extremely rare and, specifically, natural signs are often deemed as a figure of speech with no appreciable place within his thought. The objective of this paper is to counter this view and present two related points: first, Descartes’ identification of brain states with signs established by nature in the Treatise on Light (AT XI.4/G.4) amounts to a genuine attempt at understanding the causal structure of sensory perception. This is supported by Descartes’ consistent usage of the notion of sign for capturing the activities exclusive to embodied minds. Second, by reconstructing a taxonomy of signs this paper aims at rehabilitating the notion of sign as a Cartesian technical notion. It is rather perplexing that, even though Descartes made regular use of this notion in three distinct contexts, there is no general understanding of it as a term that merits rational reconstruction. This paper revises this omission with the case of sensory perception at the centre.